Forensic science and expert testimony in wrongful convictions: A study of decision-making at the Criminal Cases Review Commission - Hoyle, C (Oxford University Press, 2018)
The Criminal Cases Review Commission reviews possible wrongful convictions in England, Wales and Northern Ireland, referring back to the Court of Appeal cases where there is a ‘real possibility’ that the conviction is unsafe. This article presents findings from a four-year empirical study of decision-making within the Commission. It explores how Commission staff exercise their discretionary powers in identifying and investigating possible wrongful convictions from approximately 1,400 applications a year, referring just a few back to the Court. It focuses on a sample of cases that turned on forensic evidence and expert testimony, showing that while there is some variation in individual caseworkers’ approaches to investigation, decision-making is shaped by the law and internal policies such that reasonably consistent decision frames emerge.